Determinan Profitabilitas PT. Unilever Indonesia Tbk - Erlindawati, Erlindawati; Kismawadi, Early Ridho (BISNIS, 2019)
The purpose of this study was to determine the effect of debt to equity ratio, selection, size, and curent ratio on profitability at PT. Unilever Indonesia Tbk, which is listed on the Indonesia Stock Exchange for the period 2013-2018. The population in this study consisted of 30 companies belonging to the Jakarta Islamic Index with a 6-year research period. While the sample from this study is PT. Unilever Indonesia Tbk. Data were analyzed using multiple regression methods and using SPSS software. The results showed that partially DER had no significant effect (with a value of t -2.008 and a significant value of 0.061) on profitability. Sales do not have a significant effect (with t count -0.070 and significant value 0.945) on profitability. Size does not have a significant effect (with a t-value of -0.696 and a significant value of 0.496) on profitability. CR has a significant effect (with t count 2,249 and significant value 0,038) on profitability. Simultaneously shows that the debt to equity ratio, sales, size and curent ratio have a simultaneous effect on the dependent variable (profitability) where F count is 5.347 and F table is 2.96.